Vitamin B12 and Folate Levels During Pregnancy and Risk of Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis - Wang, Li; Hou, Yanping; Meng, Dexia; Yang, Li; Meng, Xiang; Liu, Feng (Frontiers in Nutrition, 2021)
Background: The role of vitamin B12 and folate levels with risk of gestational diabetes mellitus (GDM) is unclear. The purpose of the current study was to conduct a systematic review and meta-analysis for assessing the relationship between vitamin B12 and folate concentrations during pregnancy and the risk of GDM. Methods: PubMed, Embase, CENTRAL, and Ovid databases were searched up to 10th December 2020 for all types of studies assessing the relationship. Qualitative and quantitative analysis of data was carried out. Results: Twelve studies were included. Pooled serum vitamin B12 concentrations were found to be significantly lower in the GDM group as compared to the non-GDM group. No such difference was noted in serum folate levels. On pooled analysis of adjusted odds ratio's for risk of GDM with red blood cell (RBC) folate, serum folate, and vitamin B12 as continuous variables, no significant relationship was seen. On qualitative analysis, studies reported higher RBC folate levels with a significantly increased risk of GDM. Majority studies reported no relationship between serum folate and risk of GDM. Four of six studies reported a lowered risk of GDM with higher or normal vitamin B12 levels. Conclusion: The association between vitamin B12 and folate levels during pregnancy and the risk of GDM is unclear. Limited number of studies indicate increased risk of GDM with higher RBC folate levels, but majority studies found no association between serum folate and risk of GDM. There seems to be evidence indicative of an increased risk of GDM with vitamin B12 deficiency. There is a need for further large-scale studies from different regions worldwide to strengthen current evidence.